2021
DOI: 10.1016/j.radonc.2021.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Implementing stereotactic accelerated partial breast irradiation using magnetic resonance guided radiation therapy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…It had overall good delineation of OAR in 4D MRI images [3] , with coverage comparable to a CT examination. The analysis of the distance between the OAR showed a dominant head-feet motion in the chest and heart region when the breast (without surgery in our case) was not prone to large amplitude movements [17] , [18] , [19] in our proposed treatment setup.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…It had overall good delineation of OAR in 4D MRI images [3] , with coverage comparable to a CT examination. The analysis of the distance between the OAR showed a dominant head-feet motion in the chest and heart region when the breast (without surgery in our case) was not prone to large amplitude movements [17] , [18] , [19] in our proposed treatment setup.…”
Section: Discussionmentioning
confidence: 68%
“…Our free-breathing approach could satisfy the needs of partial breast irradiation strategies [18] , [19] , [20] . As has been shown [21] , 4D MRI using T1w GRE sequences was useful for characterizing the position of marker clips.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing clinical trial with a balloon-based single-fraction technique, which has not reported oncologic outcomes yet [ 57 ], but has reported limited severe toxicities to date. Single-fraction external beam treatments are also being developed both in the pre-operative and post-operative spaces [ 58 ]. Continued work in this space is needed to determine the ideal single-fraction dose, and long-term oncologic and toxicity outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, no additional margins for the PTV were used, minimal intrafraction motion of the tumor bed was observed [32] and a seroma reduction was documented through repeated MR scanning during the course of radiotherapy [33] , suggesting MR as an optimal imaging modality for ART in the adjuvant PBI setting. More recently, MR-guided adjuvant PBI at the 0.35 T (MRdian, ViewRay) [34] , [35] and 1.5 T MR-Linac (Unity, Elekta) [36] , [37] have been successfully delivered. Treatments could be performed in a short time, with daily plan adaptation taking on average four minutes and a cumulative in-room time of 25 min [36] .…”
Section: Mr-based Artmentioning
confidence: 99%